Counting plovers is not enough: get active in monitoring too threats and actions! (Avocetta, 2025)
Review of Mark A. Colwell and Susan M. Haig., 2020. The Population Ecology and Conservation of Charadrius Plovers. Edited by CRC Press – Taylor & Francis Group, New York, 342 pp